Does Pain Improve Earlier than Mood in Depressed Patients with Painful Physical Symptoms Treated with Duloxetine? - Hegerl, U.; Mergl, R.; Quail, D.; Schneider, E.; Hundemer, H.-P.; Linden, M. (Pharmacopsychiatry, 2012)
In depressed patients tricyclic antidepressants and selective serotonin and noradrenaline reuptake inhibitors can reduce not only depressive, but also painful physical symptoms. We investigated whether under treatment with duloxetine pain improves earlier than mood.Data were obtained within a prospective 6-month multi-centre naturalistic study in adult out-patients with depressive episodes treated with duloxetine (flexible doses: 30–120 mg/day). Pain and mood were assessed daily by visual analogue scales. For responders (n=622) “time to 50% pain response” and “time to 50% mood response” were determined by counting the earliest day between day 0 and 27, at which the patient achieved 50% improvement.Mean time to 50% pain response (mean 6.3 days, SD 5.3) was significantly shorter than time to 50% mood response (mean 7.6 days, SD 6.0, mean difference 1.3 days, SD 6.4; p<0.0001).In duloxetine-responders to both pain and mood, self-rated pain improved slightly earlier than self-rated mood. The short temporal dissociation between pain and mood improvement might be explained by an earlier conscious perception of pain than mood changes.
Keywords: antidepressants; depression; pain syndromes